2001
DOI: 10.1046/j.1365-246x.2001.01534.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of shear wave anisotropy in the crust of the southern Hyogo region by borehole observations

Abstract: SUMMAR YIn order to estimate the detailed orientation and density of cracks around an active fault area, we investigate the spatial distribution of shear wave anisotropy in the crust of the southern Hyogo region with high-quality waveform data recorded by a borehole network operated by the Geological Survey of Japan. We introduce the vertically aligned crack model of Hudson (1980Hudson ( , 1981 to explain its anisotropic structure. At stations more than 10 km away from the earthquake fault zone (i.e. Ikeda and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…For a fluid‐saturated crack, we set λ′= 2.25 × 10 9 kg m −1 s −1 and μ′= 0 as Lamé constants for the crack inclusions (e.g. Mizuno et al 2001). We search ɛ in the range 0.0005–0.02 with an increment of 0.0005 and d in the range 0.005–0.2 with an increment of 0.005.…”
Section: Resultsmentioning
confidence: 99%
“…For a fluid‐saturated crack, we set λ′= 2.25 × 10 9 kg m −1 s −1 and μ′= 0 as Lamé constants for the crack inclusions (e.g. Mizuno et al 2001). We search ɛ in the range 0.0005–0.02 with an increment of 0.0005 and d in the range 0.005–0.2 with an increment of 0.005.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it seems unlikely that the origin of anisotropy on Nokono-shima Island is the fractures of shear faults. Mizuno et al (2001) found that the LSPDs change near the end of the fault system, indicating that the LSPDs should change from parallel to the axis of maximum horizontal compressional stress to parallel to the fault strike. However, the LSPD on Nokonoshima Island is not parallel to the fault strike.…”
Section: Shear Wave Polarization Anisotropymentioning
confidence: 98%
“…Since crustal anisotropy is caused by stress-induced alignment of vertical microcracks, we can use shear wave splitting as a tool to investigate and monitor the stress beneath the seismic stations. Previous studies (e.g., Tadokoro et al 1999Tadokoro et al , 2002Mizuno et al 2001) investigated the structure of the rupture zone or its temporal changes by analyzing shear wave anisotropy. Saiga et al (2003) found temporal variation Copyright c The Society of Geomagnetism and Earth, Planetary and Space Sciences (SGEPSS); The Seismological Society of Japan; The Volcanological Society of Japan; The Geodetic Society of Japan; The Japanese Society for Planetary Sciences; TERRAPUB.…”
Section: Introductionmentioning
confidence: 99%
“…This intensive damaging causes velocity reduction and also anisotropy, and in some cases the degree of anisotropy in the fault zone is higher than that of the surrounding rocks (e.g., Mizuno et al, 2001;Watanabe et al, 2001). have found the spatial change of anisotropy in and around the aftershock region from analyzing the shear-wave splitting recorded near the source fault of the 2000 Tottori-ken Seibu earthquake MW6.6.…”
Section: Introductionmentioning
confidence: 99%